Návrat dětí z ústavní péče do rodiny v kontextu současných změn v systému péče o ohrožené děti - Sychrová, Adriana (Univerzita Pardubice, 2013)
The purpose of the article discusses reunification of children from institutional care to their birth families within the context of actual transformation of child protection system. Reunification is the process of reintegration of vulnerable child placed „out of home“ to his or her family, if it is the best interest of the child. Reunification of children placed in institutions should be a primary goal of the system because of a preference for the role of parents in the law, especially in the Convention on the Rights of the Child. The article is based on the analysis of documents of international organizations dealing with the protection of children's rights, international studies and program policy documents. The topic of reunification can be viewed from different perspectives, such as law and its influence on social policy and the practices of social work, the part of deinstitutionalization process or the decision making process. The main question is about interest of parents to care for their child. Social workers have to know characteristic of the family and the child. Then the reunification can start effectively. The family, child, specialists from institutions and social workers should participate on the process in more detail. In the conclusion of the paper the author tries to show principles and central values on which the successful process of reunification should be focused. She highlightes holistic view and complex assessment of family and safe family environment, the principle of partnership with family, the working with individual plan for child, the support of new family services, the performing sufficient preparation of the child, the family and the social environment before reuenification, intensive social services for family after returning home and finally the need for research on the process of reunification from the perspective of the child, parents and the professionals.
Reunification of children from institutions to birth family within the context of actual changes in child protection system
Keywords: reunification; child; family; child protection system; deinstitutionalisation; social services